2018
DOI: 10.1108/jmp-09-2017-0293
|View full text |Cite
|
Sign up to set email alerts
|

Self-concept orientation and organizational identification: a mediated relationship

Abstract: Purpose-The present study tests a mediated model of the relationship between self-concept orientation (individualist and collectivist) and organizational identification (OrgID, Cooper and Thatcher, 2010), with proposed mediators including the need for organizational identification (nOID, Glynn, 1998) as well as self-presentation concerns of social adjustment (SA) and value expression (VE, Highhouse et al., 2007). Design-Data were collected from 509 participants in seven countries. Direct and mediation effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Nevertheless, staff service, due to the nature of online shopping, is all done online, and consumers can only know whether the problem is solved and perceive the service received. In the case of store shopping, however, they have higher requirements for staff service and make decisions based on both the service result and whether the image of a store and its staff match their expectations [39,40]. As soon as they enter a store, consumers will start to observe the staff that approaches them in terms of their dress, presentation, and facial expressions.…”
Section: Influence Of Different Shopping Situations On the Relationshmentioning
confidence: 99%
“…Nevertheless, staff service, due to the nature of online shopping, is all done online, and consumers can only know whether the problem is solved and perceive the service received. In the case of store shopping, however, they have higher requirements for staff service and make decisions based on both the service result and whether the image of a store and its staff match their expectations [39,40]. As soon as they enter a store, consumers will start to observe the staff that approaches them in terms of their dress, presentation, and facial expressions.…”
Section: Influence Of Different Shopping Situations On the Relationshmentioning
confidence: 99%
“…relational identification with the supervisor, Sluss and Ashforth, 2007;similarity with others, Turner, 1981) as the antecedents of organizational identification. Theory and empirical evidence concerning how individual characteristics impact organizational identification have been limited, although it has been found that individual differences such as relational needs and collective-orientated characteristics may positively impact organizational identification (Gundlach et al, 2006;Guo et al, 2018;Wiesenfeld et al, 2001).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Theory and empirical evidence concerning how individual characteristics impact organizational identification have been limited, although it has been found that individual differences such as relational needs and collective-orientated characteristics may positively impact organizational identification (Gundlach et al. , 2006; Guo et al. , 2018; Wiesenfeld et al.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations